Undoing Networks - Karppi, Tero (In Search of Media, 2021)
How do we think beyond the dominant images and imaginaries of connectivity? Undoing Networks enables a different connectivity: "digital detox" is a luxury for stressed urbanites wishing to lead a mindful life. Self-help books advocate "digital minimalism" to recover authentic experiences of the offline. Artists envision a world without the internet. Activists mobilize against the expansion of the 5G network. If connectivity brought us virtual communities, information superhighways, and participatory culture, disconnection comes with privacy tools, Faraday shields, and figures of the shy. This book explores non-usage and the "right to disconnect" from work and from the excessive demands of digital capitalism.